TripAdvisor as a source of data in the planning process of tourism development on a local scale - Minkwitz, Aleksandra (Turyzm/Tourism, 2018)
The aim of this article is to answer the question of whether social networking sites can be an effective source of data, useful in the context of local tourism planning. The first part of the article contains a presentation of the role of social media in the tourism industry, a synthetic discussion of the most common topics of research related to the use of social media in tourism, and also characteristic of the TripAdvisor social network, which is the subject of the study. The second part presents the results of a study conducted using the website, covering the 30 most popular hotels, restaurants and tourist attractions in Poznan. The results contain a comment about the risks associated with the analysis of this type of data, as well as possible future directions of research.